Liberalization of trade in health services and the implication for Africa’s health system (2014)
This paper explores the relationship between trade in health services, its liberalization, and Africa's health system with particular focus on Africa. Using a sample of African countries, a regression model link, health outcomes to health inputs and health policy variables were estimated to cover two separate periods- the pre- General Agreement in Trade in Services (GATS) (1990-1994) period and GATS period (1995-2006). The coefficients of the regression are then compared to determine the impact of GATS. Increasing the public health expenditure through additional budgetary provisions in African countries improves health only at the margin. The lack of agreement in the form of GATS limited the intensity of trade in health services. The non-significance of the trade in health services proxy variables during GATS period shows that health trade services impacts on Africa's health sector should be limited to commercial presence (Mode 3) and movement of health professionals (Mode 4) which are the channels through which health services trade is conducted in many African countries. Health services trade data are limited, hence proxy measure of health services were utilised in the paper and this might blur the expected impacts. The implication of the paper is for African countries to adequately participate in GATS as it involves trade in health services.